2014
DOI: 10.1371/journal.pone.0095420
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat-Mediated Apoptosis in Human Blood-Retinal Barrier-Associated Cells

Abstract: HIV-1-associated ocular complications, such as microvasculopathies, can lead to the loss of vision in HIV-1-infected patients. Even in patients under highly active antiretroviral therapy, ocular lesions are unavoidable. Ocular complications have been demonstrated to be closely related to the breakdown of the blood-retinal-barrier (BRB); however, the underlying mechanism is not clear. The data from this study indicated that the HIV-1 Tat protein induced the apoptosis of human retinal microvascular endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…The apoptotic potential of HIV Tat has been recognized in a variety of cell types such as peripheral lymphocytes, central nervous system‐resident monocytes, astrocytes, dopaminergic and hippocampal neurons, and a range of endothelial cells—all of which presumably trigger both intrinsic and extrinsic apoptosis pathways . Consistent with these reports, we also demonstrated that Tat‐exposed Jurkat cells display a significant decrease in proliferation rate associated to an apoptosis‐like cellular profile.…”
Section: Discussionsupporting
confidence: 89%
“…The apoptotic potential of HIV Tat has been recognized in a variety of cell types such as peripheral lymphocytes, central nervous system‐resident monocytes, astrocytes, dopaminergic and hippocampal neurons, and a range of endothelial cells—all of which presumably trigger both intrinsic and extrinsic apoptosis pathways . Consistent with these reports, we also demonstrated that Tat‐exposed Jurkat cells display a significant decrease in proliferation rate associated to an apoptosis‐like cellular profile.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to pro-inflammatory mediators, they observed that retinal cells also demonstrated increased cell activation as evidenced by augmented expression of GFAP, which is due to the activation of Muller glial cells. Recent study by Che et al also emphasizes the role of HIV-1 Tat protein in the development of ocular complications during HIV infection [ 6 ]. HIV-1 Tat protein induced the apoptosis of human retinal microvascular endothelial cells and retinal pigment epithelium cells.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 Tat regulates host cell proliferation through various mechanisms including apoptosis 26 , translation 27 , 28 , and signal transduction 29 – 31 as well as mitosis 10 . Here, we provide new evidence that Tat may modulate cell proliferation by inhibiting mitosis through an interaction with RPS3.…”
Section: Discussionmentioning
confidence: 99%